2020
DOI: 10.1080/08824096.2020.1806811
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gender, religiosity and personality on the interpersonal distance preference: a virtual reality study

Abstract: Interpersonal distance (ID) is an important aspect of human nonverbal behavior. Both situational and dispositional factors play roles in interpersonal distance preference (IDP). In the present study, we investigated the effect of gender, religiosity, and Big Five personality factors on IDP in an Iranian sample. Forty-six university students watched fourteen 360-degree video clips via a virtual reality headset. In each video-clip, a male or a female actor spoke toward the camera from a particular distance and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…a Tai-Chi class). Observational studies on intersectional stigma confirmed the endurance of gender-based bias [ 63 , 64 ], and bias based on sexual orientation [ 96 ].…”
Section: Resultsmentioning
confidence: 96%
“…a Tai-Chi class). Observational studies on intersectional stigma confirmed the endurance of gender-based bias [ 63 , 64 ], and bias based on sexual orientation [ 96 ].…”
Section: Resultsmentioning
confidence: 96%
“…The same controversy appears when looking at the intervention studies carried out from a majority perspective, which mostly show a solid persistence of prejudice towards stigmatised minorities [51,55,[61][62][63][64][65][66][67][68][69] Two recent studies [70,71] even report increased prejudice towards the contacted outgroup using explicit measures.…”
Section: Types Of Contactmentioning
confidence: 99%
“…Our data included measurements of affectionate touch behaviors and love, and guided by previous findings in the area our research also comprised several individual- and culture-level predictors possibly affecting our outcomes. We selected factors used in our previous studies 6 , 39 that were shown to relate to either love [i.e., having children 40 , 41 , relationship duration 29 ] or touch [i.e., age 42 , 43 , gender, conservatism, interpersonal distance preferences 6 , socio-economic status (SES) 20 , and religiosity 6 , 44 ]. For example, touch behaviors in close interpersonal relationships are typically used more by younger, female, and liberal people 6 .…”
Section: Introductionmentioning
confidence: 99%